The Powers of Sound and Song in Early Modern Paris - Hammond, Nicholas (Perspectives on Sensory History, 2021)
The long and spectacular reign of Louis XIV of France is typically described in overwhelmingly visual terms. In this book, Nicholas Hammond takes a sonic approach to this remarkable age, opening our ears to the myriad ways in which sound revealed the complex acoustic dimensions of class, politics, and sexuality in seventeenth-century Paris.The discovery in the French archives of a four-line song from 1661 launched Hammond's research into the lives of the two men referenced therein-Jacques Chausson and Guillaume de Guitaut. In retracing the lives of these two men (one sentenced to death by burning and the other appointed to the Ordre du Saint-Esprit), Hammond makes astonishing discoveries about each man and the ways in which their lives intersected, all in the context of the sounds and songs heard in the court of Louis XIV and on the streets and bridges of Paris. Hammond's study shows how members of the elite and lower classes in Paris crossed paths in unexpected ways and, moreover, how noise in the ancien régime was central to questions of crime and punishment: street singing was considered a crime in itself, and yet street singers flourished, circulating information about crimes that others may have committed, while political and religious authorities wielded the powerful sounds of sermons and public executions to provide moral commentaries, to control crime, and to inflict punishment.This innovative study explores the theoretical, social, cultural, and historical contexts of the early modern Parisian soundscape. It will appeal to scholars interested in sound studies and the history of sexuality as well as those who study the culture, literature, and history of early modern France